Aflatoxin contamination in sweet potato products: implications for consumer health and food safety in Pakistan - Iqbal, Shahzad Zafar; Abdull Razis, Ahmad Faizal; Waseem, Muhammad; Mohammad, Osama A.; Ali, Sajad; Mousavi Khaneghah, Amin (Springer Science and Business Media Deutschland GmbH, 2025)
Aflatoxins (AFs), especially aflatoxin B1, are carcinogenic mycotoxins that contaminate food crops, presenting a considerable risk to human health. The study aimed to investigate the prevalence of aflatoxin B1 and total AFs in commercially available and ready-to-eat sweet potato samples from Punjab, Pakistan, to quantify contamination levels and assess dietary exposure. A total of 480 commercial sweet potato samples and 365 ready-to-eat sweet potato samples were collected and tested with High-Performance Liquid Chromatography (HPLC). The samples were obtained from multiple cities in Punjab, such as Daska and Kila Soba Singh. The investigation revealed that 28.5% of commercial sweet potato samples and 19.7% of ready-to-eat sweet potato samples contained AFs. The highest average concentrations of total AFs were observed in commercial samples (28.5 ± 4.2 µg/kg) and in ready-to-eat samples (14.50 ± 2.50 µg/kg) from Daska. Furthermore, 40% of commercial samples from Jamki had AF levels ranging from 1 to 10 µg/kg, and 13.3% of samples from Kila Soba Singh surpassed 20 µg/kg. The dietary intake assessment revealed that the highest exposure (3.16 µg/kg body weight/day) occurred in female subjects aged 21–30 years. The results underscore considerable AF contamination in sweet potatoes, emphasizing the need for improved storage methods to reduce exposure. Regulatory measures and awareness initiatives must be implemented to ensure food safety and mitigate health hazards associated with AF contamination.